Determinan Faktor Stunting Pada Anak Balita di Darul Imarah Aceh Besar, Indonesia - Aripin Ahmad (JURNAL RISET GIZI, 2022)
Stunting is a disorder of growth and development of children affected by chronic nutrient deficiency, repeated infections and lack of stimulation during the first 1000 days of a child's life. This study aims to examine the effect of breastfeeding and birth weight with the incidence of stunting in children under five. The case control study design was used for 116 children under five, namely 53 cases and 53 controls, in the working area of the Darul Imarah Health Center Aceh Besar. Data characteristics, early brestfeeding initiation, exclusive breastfeeding, duration of breastfeeding were collected by interview method, birth weight was collected from birth records in the MCH book, and stunting data was collected by anthropometric measurements determined by the HAZ index based on the z-score, stunting if the z-score value -2 SD. Data analysis was performed bivariate and multivariate using binary logistic regression test at 95% confidence level. The results showed that exclusive breastfeeding and LBW were risk factors for stunting in under five children. Children who are not exclusively breastfed are at risk of 4.57 times greater risk of stunting than children who are exclusively breastfed (OR=4.57; 95% CI; 1.57-13.27), and children born with low birth weight have a 9.43 times greater risk of stunting than children born with normal weight (OR=9.43: 95% CI; 3.54-25.12). Efforts are needed to increase the coverage of exclusive breastfeeding through education and promotion of breastfeeding, as well as improving the health of pregnant women to prevent LBW babies, so as to reduce the incidence of stunting. since early stage.